(untitled) (Revista de Estudos da Linguagem, 1996)
This article is a contribution to the study of the role played by pragmatic factors in negation in Brazilian Portuguese. It is shown that cultural factors, such as Leech’s Politeness Maxims, play an important role in the use of negation by Brazilian Portuguese speakers and that these aspects must be taken into consideration in the teaching of Brazilian Portuguese as a foreign language.